Blockchain applications and smart contracts (LiveLessons (Indianapolis, Ind.), 2019)
"The Blockchain and cryptocurrency are important tools for a decentralized market that needs to protect its speed, security, and reputation. Blockchain technologies are being researched by the largest corporations to securely transact and run their business. The concept of smart contracts, micro finance, and transparent transactions are all benefits of the Blockchain. This course will provide a developer the techniques necessary to write applications that run on a Blockchain."--Resource description page